1990
DOI: 10.1152/ajpcell.1990.259.4.c687
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying magnetic fields increase cytosolic free Ca2+ in HL-60 cells

Abstract: Electromagnetic fields have been reported to cause a variety of biological effects. It has been hypothesized that many of these phenomena are mediated by a primary effect on the concentration of cytosolic free calcium ([Ca2+]i). We investigated the effects of exposure to electromagnetic fields on [Ca2+]i in HL-60 cells using the Ca2(+)-sensitive fluorescent indicator indo-1. Indo-1-loaded cell samples were exposed to a radiofrequency electromagnetic field, a static magnetic field, and a time-varying magnetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(61 citation statements)
references
References 22 publications
3
55
1
2
Order By: Relevance
“…Experiments with different cell types consistently point to the Ca 2ϩ signaling system as the primary cellular target of MF interactions (5,10,23,52,53,60,69,86,87). In many cases, alternating MFs alone or in combination with static fields increase intracellular Ca 2ϩ , as, for instance, in HL60 cells (10), T-lymphocytes and leukemia cells (60), the human T cell line (Jurkat) (55,56), bone cells (23), pituitary cells (5), and human astrocytoma cells (69).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 99%
“…Experiments with different cell types consistently point to the Ca 2ϩ signaling system as the primary cellular target of MF interactions (5,10,23,52,53,60,69,86,87). In many cases, alternating MFs alone or in combination with static fields increase intracellular Ca 2ϩ , as, for instance, in HL60 cells (10), T-lymphocytes and leukemia cells (60), the human T cell line (Jurkat) (55,56), bone cells (23), pituitary cells (5), and human astrocytoma cells (69).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 99%
“…The physical coupling between calcium signaling and EMFs could be the result of ion-protein interactions [38,39] or from the effect of the induced electric currents in the signaling [40]. Many authors propose that calcium itself as an ion is the primary target of EMFs during the initial step of coupling [41,42,43,44]. In addition, other forms of stimulation where calcium provokes the activation of downstream signaling pathways include exercise in the form of muscle stretch [45,46] and shear stress through fluid flow [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…The calcium ion is an important intracellular signal that is involved in many cellular pathways. It is associated with lymphocyte activation (10,25), and many studies have reported the biological effects of static or pulsed magnetic fields on membrane ion transport. The influence of magnetic fields on the movement of calcium ion in the context of membranes could explain the diversity and variety of cellular responses observed in cell proliferation, cell differentiation and release of cytokines.…”
Section: Discussionmentioning
confidence: 99%